Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

“As a person, I feel I’ve changed pretty immensely”: Sojourners’ aspirations and self-perceived achievements - Müller, Mareike (The Canadian Modern Language Review)
This article explores the interplay between learners’ linguistic and personal objectives as well as evaluations of their achievements in study-abroad contexts, an area that has thus far remained widely unexplored given the prevalence of product-oriented, outcomes-based research. The study draws on the case of one Canadian student of German who studied abroad at a German university for one year. To adopt an emic perspective, the data gained from a learning history questionnaire, semi-structured interviews, and e-journals were analyzed and interpreted within the framework of narrative analysis. The results show not only that learners’ sojourn objectives may be complex, dynamic, and contradictory in nature but also that they need to be examined beyond their face value, as they are entangled with learners’ negotiations of desirable subject positions and attempts to integrate their sojourn experiences, successes, and frustrations in a coherent and positive life narrative.
Keywords: individual differences; learner beliefs; narrative analysis; sojourn objectives and evaluations; study abroad

Mathematics-related Competence of Early Childhood Teachers Visiting a Continuous Professional Development Course: An Intervention Study - Bruns, Julia; Eichen, Lars; Gasteiger, Hedwig (Mathematics Teacher Education and Development (MTED))
Recent studies highlight early childhood teachers’ mathematics-related competence. Developing this competence should be a main aspect of early childhood teachers’ education. This is, however, not the case in all countries. Consequently, high-quality professional development courses are needed. Based on research results, we developed a competence-oriented continuous professional development course ("EmMa") and examined the effects of "EmMa" by asking: How does "EmMa" affect the development of early childhood teachers’ i) mathematical content knowledge, ii) mathematical pedagogical content knowledge and iii) beliefs towards mathematics in general? To answer these questions, we conducted a pre-test/post-test study including a control group with 99 in-service early childhood teachers. Results show that the course affected teachers’ mathematical pedagogical content knowledge and static orientation towards mathematics positively. From this we conclude that scaling-up "EmMa" might be a suitable approach to bridge the gap between pre-service education with nearly no mathematics and the challenges of early mathematics education.
Keywords: Beliefs; Competency Based Teacher Education; Control Groups; Early Childhood Education; Faculty Development; Foreign Countries; Inservice Teacher Education; Intervention; Mathematical Aptitude; Mathematics Skills; Pedagogical Content Knowledge; Preschool Teachers; Pretests Posttests; Professional Continuing Education; Statistical Analysis; Teacher Competency Testing

Listening to learners’ voices: Qualitative aspects of pronunciation learning during study abroad - Müller, Mareike (Journal of Second Language Pronunciation)
This article investigates learners’ perceptions on pronunciation learning in study-abroad contexts from a qualitative perspective. While previous research focused mainly on quantitative measurements of pronunciation gains with mixed results, this study takes a more learner-centered approach and examines the impact of socio-psychological factors on learning foreign pronunciation, which appears to be a highly individual and at times conflict-prone process with which sojourners are confronted. The study draws on the cases of five Canadian students who studied abroad at German universities for one or two semesters. The data collection involved a learning history questionnaire; semi-structured interviews pre-, mid-, and post-sojourn; and bi-weekly e-journals. The data was analyzed and interpreted within the framework of narrative analysis. The results show how sojourners’ beliefs about the importance of pronunciation, community participation, identity-related challenges, and obstacles to pronunciation learning influence and help explain individually different learning behaviors and results.
Keywords: pronunciation learning; study abroad; qualitative approach; narrative analysis; learner beliefs; socio-psychological learning factors